The Significance of Debt Policy as a reinforcement factor in the Effect of Managerial Ownership and Profitability Toward Company Value - Siti Epa Hardiyanti; Akhmadi (PT Larva Wijaya Penerbit, 2022)
The research aims to determine whether there are effects between managerial ownership and profitability on companyvalue, by using debt policy as intervening variable. The type of research used descriptive and associative research.The research population was manufacturing companies listed in Indonesia Stock Exchange (IDX) period of 2011-2015 as many as 80 companies. By using purposive sampling method, 25 companies as sample were obtained. The data used secondary data. Dataanalysis used classical assumption test, path analysis and partial test (t-test), using SPSS (Statistics Product andService Solution) 17 for windows. The results indicate that there are no effects of managerial ownership on companyvalue, there are positive and significant effects of profitability on company value, there are no effects of debt policy on company value, there are positive and significant effects of managerial ownership on debt policy, there are negativebut not significant effects of profitability on debt policy, there are no effect of managerial ownership on company value with Debt Policy mediated, there are negative effects of profitability on company value with Debt Policy mediated